Public expenditures and poverty: evaluation of the government’s priority programs in Gorontalo Province - Muh. Amir Arham; Tresya F. Naue (Universitas Islam Indonesia, 2015)
Private investments and exports are still limited to drive the economy of Gorontalo, therefore the government expenditures are certainly needed as a driver for the economic growth which in turn reduce the poverty. This research aims to test the effect of public expenditures on education, health, and infrastructure toward poverty. The research used econometric analysis of panel data of regencies/city in Gorontalo, 2009-2013. The results demonstrated that public expenditures on education and health had negative and significant effects toward the poverty level in all regencies/city in Gorontalo while the public expenditure on infrastructure did not have any effect toward the level of poverty in all regencies/city in Gorontalo.